The Effect of COVID-19 on Supply Chain Management: Pre and Post-COVID-19: Case Study of CVS Pharmacy, Inc. - Ochonogor, Kenechukwu Nwuka; Osho, G. Solomon; Anoka, Cyril O.; Uwakonye, Matthew (International Journal of Management Innovation Systems, 2024)
Throughout the COVID-19 crisis, everyone has observed many disruptions in the pharmaceutical supply chain. Indeed, this global and complex supply chain is vulnerable, especially when it must face a sudden rise in global demand. To adapt to the increasing demand and the numerous shortages, the United States White House has suggested several recommendations (The White House, 2021). Three of them will be detailed in this report: boosting local production, building an emergency capacity, and promoting international cooperation. With more than 10,000 locations and retail stores in the United States and with the competition of large retail stores like Target and Walmart, CVS has continued to enhance its supply chain by rolling out vendor technological portals designed to facilitate its supply chain programs and models. Most of CVS’s generic products and retail merchandise are manufactured outside the United States. To ensure the sustainability and efficiency of their models, integrated planning, internal and external collaborations, and dissemination of forecasting models with suppliers help them to predict and manage demand uncertainties. CVS is digitally connected to give people more options by using their artificial intelligence platform, thereby harnessing the power of digital technology and the Omni channel sourcing to ensure that their customers are reached/served whenever, and by whatever means possible. During the COVID-19 pandemic, CVS faced three major issues related to the distribution of common drugs between patients with chronic illnesses and patients with COVID-19 pneumonia, a high volume of customer calls, and high procurement costs of medicines from suppliers due to shortages. This led CVS to implement temporary mitigation measures that set it apart from its competitors and helped serve more patients in an orderly fashion. Based on the learnings from CVS, this report presents a set of short-term solutions that can be implemented by CVS to insulate it from future shortages until the long-term solutions are implemented in collaboration with the FDA and drug suppliers.